Synthesis and characterisation of multi-substituted thiourea derivatives and their antibacterial activities - Wan Sharifatun Handayani, binti Wan Zullkiplee (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Two series of bis-substituted thiourea derivatives 40a-e and tri-substituted thiourea derivatives 42a-i have been successfully synthesised by reaction of isothiocyanate intermediates with series of amines. 1,3-benzenedicarbonyl chloride 9 and 1,3,5- benzenetricarbonyl chloride 46 were utilized as a scaffold to prepare the isothiocyanate intermediates and formed 40a-e and 42a-i respectively. The synthesis of proposed hexasubstituted thiourea derivatives was done by reacting hexachlorocyclotriphosphazene 4 as a precursor and formed six unexpected thiourea derivatives 43a-f. The preparation of unexpected thiourea products was triggered by the formation of HCl in the reaction system due to existence of free chlorine atoms which mildly dissociated from 4. The synthesis of the proposed hexa-substituted thiourea derivatives was continued via aminolysis reaction of 4 with single thiourea compounds 43a-i but the reaction was unsuccessful. All synthesised products were characterised using CHNS elemental analysis, FTIR, 1H NMR, 13C NMR and 31P NMR spectroscopic techniques. Antibacterial assay of all synthesised products was carried out using turbidimetric method against the growth of Escherichia Coliform sp. (E. coli). The results indicated that only compounds 42a-i which bear three thiourea moieties showed significant antibacterial activities. The effects of constituents and structure of the investigated compounds on the antibacterial performance were discussed.